The Physical and Chemical Properties of Fine Carbon Particles-Pinewood Resin Blends and Their Possible Utilization - Aviwe Melapi; Sampson N. Mamphweli; David M. Katwire; Edson L. Meyer (Journal of Chemistry)
The application of biomass gasification technology is very important in the sense that it helps to relieve the dwindling supply of natural gas from fossil fuels, and the desired product of its gasification process is syngas. This syngas is a mixture of CO and H2; however, by-products such as char, tar, soot, ash, and condensates are also produced. This study, therefore, investigated selected by-products recovered from the gasification process of pinewood chips with specific reference to their potential application in other areas when used as blends. Three samples of the gasification by-products were obtained from a downdraft biomass gasifier system and were characterized in terms of chemical and physical properties. FTIR analysis confirmed similar spectra in all char-resin blends. For fine carbon particles- (soot-) resin blends, almost the same functional groups as observed in char-resin blends appeared. In bomb calorimeter measurements, 70% resin/30% char blends gave highest calorific value, followed by 50% resin/50% soot blends with values of 35.23 MJ/kg and 34.75 MJ/kg consecutively. Provided these by-products meet certain criteria, they could be used in other areas such as varnishes, water purification, and wind turbine blades.